Manifestasi Seksualitas Dalam Budaya Kebebasan - Rusydi Hikmawan (Ulumuna, 2006)
his time, pornography and erotic actions start to correlate into culture domain, where human beings become the subject as well as the object. Concept of culture claims the relationship between human interaction on society and culture as a result of them. Pornography and erotic actions are considered to be the representation of the products of human being activities in the forms of technology, pictures, idols, painting etc. All of them are then absorbed into culture. The opponents of freedom culture suggest that Indonesian people should be responsible to the development of Indonesian culture which is based on religions and eastern norms. The most dominant norms is Islamic teaching which is the religion of the majority of the citizen. Thus, Indonesia culture should be able to represent Islamic way of life which is based on al Quran and Sunnah. Pornography, which is against Islamic teaching should not be part of Indonesian culture.